Pengaruh Ukuran Perusahaan, Profitabilitas, Dan Reputasi Kap Terhadap Audit Delay - Lubis, Ivan Geovani S.; Pusposari, Devy (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2023)
Audit delay refers to the time required to complete the issuer's financial statements starting from the financial closing date of the financial year to the issuance date of the auditor's report. This study aims to determine the effect of company size, profitability, and Public Accounting Firm reputation on audit delay. The objects include non-primary consumer sector companies listed on the Indonesia Stock Exchange between 2019 and 2021. This study includes 291 samples selected through the purposive sampling technique and analyzes secondary data quantitatively by testing the effect between variables through multiple linear regression utilizing Statistical Product and Service Solution (SPSS) data processing program version 26. The results of this study indicate that the data on firm size is not sufficient to prove that there is an effect on audit delay, while profitability and Public Accounting Firm reputation have a negative effect on audit delay.